Latin American IR and the primacy of lo práctico (2008)
This article traces the general historical development of international relations (IR) thinking in Latin America based upon the influence of key intellectual, political, economic, social, and cultural factors. In particular, the ways in which state needs, foreign policy practices, the development of the social sciences, and US IR knowledge have influenced Latin American understandings of the “international” since the postwar period are explored.